Towards a Sustainable Anti-Corruption Strategy: An Ethic-Induced Model - Adoko Obicci, Peter (Management Studies and Economic Systems, 2016)
Literature abounds to show that the current anti-corruption strategies have failed to fight corruption because of neglect of ethics in these strategies, despite its importance. The purpose of this paper is to make a contribution to anti-corruption theory by developing a model that clarifies many complex ethical dilemmas around corruption. To develop a conceptual model, the extant literatures on ethics and anti-corruption strategy were used. Specifically, the focus was on the constructs of the complexity of fighting corruption by suggesting and analyzing ethical integrity, reasoning, and competence and the existing models of anti-corruption strategies. Surprisingly, anti-corruption literature has not yet adequately considered the concept of ethics in fighting corruption. In this paper, an ethics-induced model of anti-corruption strategy was developed, which identifies three types of ethical measures to combat corruption- integrity, reasoning and competence. Ethical integrity is likely to determine how an individual employee behaves in a volatile environment and where such an individual can easily be lured into corruption. Ethical reasoning would enable an individual to have a precise moral judgment. However, ethical competency is more likely to direct how an individual ought to act with a high degree of outdoing the temptations to corrupt. This paper is a conceptual one and has not been empirically validated yet. The results are to be viewed as preliminary that necessitates further extensive empirical research. However, the model has implications for further research. Scholars and researchers may empirically test the extent to which ethical integrity, reasoning, and competence can ably fight corruption. They may also test the potential effects of anti-corruption strategies and tactics as well as ethical dilemmas corruptors face. Knowing the cause and nature of corruption may help to select the appropriate anti-corruption strategy given then it is committed by persons who are moral beings. For instance, when corruptors face high corruption temptation scenario, they may be well advised to select ethical reasoning to handle the dilemma. The value of the present article lies in the fact that it binds together the literature on ethics and corruption. Thus, the paper helps reduce the artificiality of the current anti-corruption strategies.
Keywords: Corruption; Developing economies; Ethics; Ethical integrity; Ethical competency; Ethical reasoning